2003
DOI: 10.1104/pp.103.030692
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria Toxin-Mediated Cell Ablation Reveals Interregional Communication during Arabidopsis Seed Development

Abstract: Fertilization of the female gametophyte in angiosperm plants initiates a process of coordinated development of embryo, endosperm, and seed coat that ensures the production of a viable seed. Mutant analysis has suggested that communication between the endosperm and the seed coat is an important determinant in this process. In addition, cell groups within the embryo, derived from the apical and from the basal cell, respectively, after zygote division, concertedly establish a functional root meristem, and cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 52 publications
2
133
0
Order By: Relevance
“…In addition, some available data are contradictory. Expressing LTP1::DTA (LTP1, lipid transfer protein 1; DTA, diphtheria toxin A chain) in the protoderm domain of embryos (21) to injure the embryo protoderm can induce excessive divisions in the suspensor (22). However, expression of the LTP1-driven BARNASE (Bacillus amyloliquefaciens ribonuclease) gene in the embryo, which results in defects in the basal tier of the embryo and hypophysis, leads to no signs of deregulation of suspensor development (23).…”
mentioning
confidence: 99%
“…In addition, some available data are contradictory. Expressing LTP1::DTA (LTP1, lipid transfer protein 1; DTA, diphtheria toxin A chain) in the protoderm domain of embryos (21) to injure the embryo protoderm can induce excessive divisions in the suspensor (22). However, expression of the LTP1-driven BARNASE (Bacillus amyloliquefaciens ribonuclease) gene in the embryo, which results in defects in the basal tier of the embryo and hypophysis, leads to no signs of deregulation of suspensor development (23).…”
mentioning
confidence: 99%
“…No significant growth of the seed coat is observed in seeds in which only the egg cell is fertilized as a result of the production of a single sperm cell in A-type cyclin-dependent kinase1 mutant pollen (Nowack et al, 2006). Similarly, ablation of endosperm in developing seeds results in extremely reduced seed coat development (Weijers et al, 2003). Thus, we propose that fertilization of the egg cell and consequent embryo development may not play a major role in seed coat growth.…”
Section: Discussion Fertilization Enhances Cell Proliferation and Trimentioning
confidence: 83%
“…The major phase of seed growth parallels the initial endosperm growth characterized by rapid successive rounds of mitoses devoid of cytokinesis (syncytial development) (Garcia et al, 2005). Specific production of diphtheria toxin A in the developing endosperm caused a rapid arrest of seed growth (Weijers et al, 2003). Genetic analyses of the HAIKU pathway revealed that reduced syncytial endosperm growth prevents cell elongation in the seed coat, leading to smaller seeds (Garcia 1 To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, such checkpoint behavior was previously not found in plants in which the endosperm was genetically ablated, and Weijers et al (2003) found that embryogenesis could continue with very little endosperm although these embryos would eventually arrest. The driver line used for these ablation experiments becomes expressed 2 DAP, and a possible explanation is that this expression is already later than a putative seed size checkpoint.…”
Section: Discussionmentioning
confidence: 99%